Meningkatkan Kepercayaan Diri Siswa Menggunakan Bimbingan Kelompok Dengan Teknik Sosiodrama Peserta Didik SMA N 4 Palangka Raya: Improving Self-Confidence Of Students Using Group Bimbing With Participants Of Sociodrama Techniques In Sma N 4 Palangka Raya - Esthi Puspitarini; Mohammad Fatchurahman (Suluh: Jurnal Bimbingan dan Konseling, 2017)
The purpose of this study was to determine whether group counselling with sociodrama techniques could improve students' self-confidence. The research methodology used is the experiment. The population in this study was four palangkaraya public high school students. There is an increase in students 'self-confidence after the pre-test and post-test means "Guidance for Sociodrama Techniques To increase students' self-confidence in Palangka Raya N-4 High School". Intervention in the form of a post-test. The results of the pre-test and post-test test can be calculated to obtain information that the value of Asymp. Sig. (2-tailed) Is 2.539. Because of the amount of Asymp. Sig. ˂ real level (α / 2 = 0.11) then Ho is rejected, and Ha is accepted. That means there is an increase in students' self-confidence after the pre-test and post-test. The analysis shows that students in the experimental group experienced an increase in scores from before getting a pre-test intervention 43% and after getting an intervention in the form of a 70% post-test, so It is known that sociodrama techniques can increase the confidence of Palangka Raya N-4 High School students